2013
DOI: 10.1371/journal.pone.0062686
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Providers’ Offering and Patients’ Acceptance of HIV Screening in Emergency Departments: A Multilevel Analysis. ANRS 95008, Paris, France

Abstract: ObjectiveWe assessed the EDs’ characteristics associated with the offer and acceptance rates of a nontargeted HIV rapid-test screening in 29 Emergency Departments (EDs) in the metropolitan Paris region (11.7 million inhabitants), where half of France’s new HIV cases are diagnosed annually.MethodsEDs nurses offered testing to all patients 18–64-year-old, able to provide consent, either with or without supplemental staff (hybrid staff model or indigenous staff model). The EDS’ characteristics collected included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies evaluating nurse-driven HIV screening, compared to screening performed by other health care staff, showed a trend in higher test offering, better acceptance and higher delivery rates with the implementation of nurse-driven HIV screening [ 24 ]. However, a progressive decrease in test offering rates from nurses and other staff over time has been observed, most likely resulting from of a loss of motivation related to the small number of new diagnoses, which were concentrated in patients at high risk of HIV exposure [ 20 , 25 , 26 ]. It has been suggested that nurse-driven HIV screening in EDs was possible on a wider scale over the long-term but would be more feasible if it targeted a specific patient population [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating nurse-driven HIV screening, compared to screening performed by other health care staff, showed a trend in higher test offering, better acceptance and higher delivery rates with the implementation of nurse-driven HIV screening [ 24 ]. However, a progressive decrease in test offering rates from nurses and other staff over time has been observed, most likely resulting from of a loss of motivation related to the small number of new diagnoses, which were concentrated in patients at high risk of HIV exposure [ 20 , 25 , 26 ]. It has been suggested that nurse-driven HIV screening in EDs was possible on a wider scale over the long-term but would be more feasible if it targeted a specific patient population [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this study was not designed to capture the number of patients who opted out, most participants stated that patients rarely declined (except for people who did not want to have blood tests done at all or reported that they were HIV positive). Studies from diverse settings around the world have shown high patient acceptance of opt-out HIV testing (Haukoos et al 2008;Wilson d'Almeida et al 2013;Montoy et al 2016). This is the first Australian study to demonstrate that marginalised patients are accepting of the opt-out method.…”
Section: Discussionmentioning
confidence: 80%
“…We observed that accessibility to voluntary testing as a protective factor to HIV and universal access to serological screening, including HIV are components associated with prevention and reduction in the chain of transmission. Data from a European study offering testing in emergency services associated the lower propensity of test acceptability among young people who perceived themselves to be at reduced risk of HIV or if they had been previously tested ( 44 ) .…”
Section: Discussionmentioning
confidence: 99%